A study to derive a preliminary clinical decision rule for investigation of patients suspected of having acute coronary syndrome - Hess, Erik Paul (University of Ottawa (Canada), 2008)
Objective. We derive a preliminary clinical decision rule to identify which patients with chest pain can be safely discharged without cardiac stress testing. Methods. We prospectively enrolled patients over 24 years of age with chest pain. The primary outcome was acute myocardial infarction, revascularization, or 30-day mortality. Results. We enrolled 640 patients. Characteristics were: mean age 59.6 years, 40.2% female and 21.9% history of acute myocardial infarction. There were 87 positive outcomes. We derived a rule which consisted of 5 variables: known coronary artery disease, age ≥ 55 years, acute ischemic changes on electrocardiogram, cardiac troponin T ≥ 0.01 ng/mL, and diaphoresis. The rule was 100% (95% CI 96-100%) sensitive and 25% (22-25%) specific for adverse cardiac events. Conclusion. We derived a preliminary decision rule that is highly sensitive for adverse cardiac events. Additional research is required to derive a definitive decision rule.
Keywords: Health Sciences, Epidemiology.